Magnetic phase transition of mechanically alloyed single sample Co0.5Ni0.5Fe2O4 - Low, ZH; Ismail, I; Shafie, MSE; Ibrahim, IR; Ertugrul, M; Azis, RS; Saiden, NM; Hasan, IH; Idris, FM; Nazlan, R (Elsevier, 2024)
Indexed by WOS/Scopus/ERA